2018
DOI: 10.1016/j.lrp.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Alliance governance choices: Disentangling the effects of uncertainty and alliance experience

Abstract: This article analyses the interaction between alliance experience and behavioural uncertainty to improve our understanding of alliance governance. We investigate the extent to which the effect of alliance experience on governance choices is explained by a reduction in "mundane" transaction costs or by a reduction in "opportunistic" transaction costs. Based on more than 12,000 firm experiences with equity and non-equity alliances, we demonstrate a reduction in mundane transaction costs over time by firms reusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…A focal firm that collaborates with partners at a large cultural or geographical distance will experience information asymmetry, which increases the chance that partners will appropriate a disproportionate share of the rents or resources from the IOR (Li et al . ; Niesten and Jolink ; Wang and Zajac ). Similar difficulties have been reported for collaborations with unfamiliar partners or partners with incongruent goals (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A focal firm that collaborates with partners at a large cultural or geographical distance will experience information asymmetry, which increases the chance that partners will appropriate a disproportionate share of the rents or resources from the IOR (Li et al . ; Niesten and Jolink ; Wang and Zajac ). Similar difficulties have been reported for collaborations with unfamiliar partners or partners with incongruent goals (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In our literature review, we have identified several examples that relate to plurality of views, such as collaborating with partners from different countries, cultures, industries and sectors (Bolivar‐Ramos ; Colombo and Piva ; Niesten and Jolink ; Perkmann and Schildt ), or collaborating with competitors (i.e. coopetition) (Hallen et al .…”
Section: Resultsmentioning
confidence: 99%
“…Joint ventures are legally described as common venturing for profit under common control with each partner participating in profits and losses (Hale, 1956). They involve the formation of new and separate business entities (Niesten and Jolink, 2018), and are 'evaluated primarily as stand-alone entities seeking to maximize their own performance' (Anderson, 1990, p. 23). Joint ventures are tightly coupled forms of organizing in which the parent companies are linked together by formal structures (e.g.…”
Section: Structures Of Environmental Alliances: Economic Versus Envir...mentioning
confidence: 99%
“…In a comparative approach, a major difference between joint ventures and contracts is that joint ventures offer more safeguards against opportunistic behavior than contractual agreements (Oxley, 1997;Jolink and Niesten, 2016;Niesten and Jolink, 2018). They have been described as more protective governance structures (Oxley and Sampson, 2004) due to their administrative controls and incentive alignment via equity and profit sharing among partners (Oxley, 1997).…”
Section: Structures Of Environmental Alliances: Economic Versus Envir...mentioning
confidence: 99%
See 1 more Smart Citation